THE INFLUENCE OF SOCIO-ECONOMIC FACTORS ON POVERTY IN BALI PROVINCE - MURTHI, NGURAH WISNU (Universitas Mahasaraswati K. Mataram, 2023)
The aim of this research is to find out 1) To find out whether unemployment has a partial effect on the level of poverty in Bali Province; 2) To find out whether the minimum wage has a partial effect on the poverty level in Bali Province; 3) To find out whether unemployment and the minimum wage have a simultaneous effect on the poverty level in Bali Province. The socio-economic factors that will be studied are unemployment and minimum wages. The research was conducted in Bali Province. The quantitative data in this research were unemployment, minimum wages and poverty levels for the 2007-2021 period. The data source in this research is secondary data. The data analysis techniques used to solve the problems in this research are: 1) Classic Assumption Test which includes: Normality Test, Multicollinearity Test, Heteroscedasticity Test and Autocorrelation Test, 2) Hypothesis Testing using Multiple Linear Regression Analysis Techniques.Based on the results of the analysis, it is known that with a confidence level of 79.4 percent, all independent variables have a simultaneous or partial effect on the dependent variable. This means that socio-economic factors consisting of unemployment and minimum wages influence the poverty level in Bali Province both simultaneously and partially. If we look at the coefficient of determination, only 79.4 percent of the variation in unemployment and minimum wages can explain the variation in poverty levels in Bali Province. This is because there are many other factors that influence the level of poverty in Bali Province, including other socio-economic factors that are not discussed in this research